The deterrent effect of curfews: an evaluation of juvenile probationers - Urban, Lynn S. (Criminal justice recent scholarship, 2007)
Juvenile court history and trends -- The nightwatch program -- Theories of crime control and evidence of juvenile program effectiveness -- Obtaining a sample of active juvenile offenders -- Does Nightwatch work? -- Identifying "deterrable" offenders -- The future of curfew enforcement